Principles of Guided Bone Regeneration in Dentistry and Maxillofacial Surgery: Evolution of the Concept and Biological Mechanisms (Review) - Astapenko, О. О.; Rozhnov, А. С. (Actual Dentistry, 2025)
Introduction. Guided bone regeneration (GBR) is a highly effective method for the restoration of bone defects, widely used in dentistry and maxillofacial surgery. The growing demand for implant treatment stimulates the development of advanced barrier membranes. Objective. To summarize current understanding of the principles of guided bone regeneration, highlight the biological foundations of the method, its historical development, molecular mechanisms of osteogenesis and angiogenesis, and assess the prospects for new barrier materials. Material and methods. The information search and analysis of scientific sources was conducted using scientometric databases including Web of Science, PubMed, Google Scholar, Scopus, SpringerLink, ScienceDirect, and Wiley Online Library, covering publications from the past 50 years. Conclusions. The GBR method enables controlled and effective bone regeneration by isolating the defect and stimulating osteogenesis. The choice of membrane depends on clinical conditions, biocompatibility, and biodegradability. Innovative polyurethane membranes show high potential due to their mechanical stability and functionalization capability. The future of GBR lies in integrating molecular technologies, advanced materials, and personalized treatment approaches.